2009
DOI: 10.1103/physrevb.79.064517
|View full text |Cite
|
Sign up to set email alerts
|

Band renormalization and Fermi surface reconstruction in iron-based superconductors

Abstract: Using the fluctuation exchange approximation and a three-orbital model, we study the band renormalization, the Fermi surface reconstruction, and the superconducting pairing symmetry in iron-based superconductors. We find that the interorbital spin fluctuations lead to the strong anisotropic band renormalization and the renormalization is orbital dependent. As a result, the topology of Fermi surface displays distinct variation with doping from the electron type to the hole type, which is consistent with the rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 42 publications
5
43
0
Order By: Relevance
“…86 We note that there are several alternative three-orbital models which display an xy-dominated hole pocket at the M point. 44,53 A similar analysis to that performed here has been carried out for such a three-orbital model, 62 and the susceptibility was found to be peaked at an incommensurate wavevector close to (π, 0). More recently, Zhou and Wang studied a three-orbital model of LaFeAsO using Gutzwiller mean-field theory restricted to two-site magnetic unit cells and found significant deviations from the usual Hartree-Fock approach.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…86 We note that there are several alternative three-orbital models which display an xy-dominated hole pocket at the M point. 44,53 A similar analysis to that performed here has been carried out for such a three-orbital model, 62 and the susceptibility was found to be peaked at an incommensurate wavevector close to (π, 0). More recently, Zhou and Wang studied a three-orbital model of LaFeAsO using Gutzwiller mean-field theory restricted to two-site magnetic unit cells and found significant deviations from the usual Hartree-Fock approach.…”
Section: Resultssupporting
confidence: 72%
“…81 Although the existence of superconductivity in these models has been extensively studied, 40,[44][45][46]48,51,53,56,60,63,64,66 the magnetic behaviour remains rather poorly understood. The most popular approach to the appearance of AFM order in these models is to examine the ground state using a standard mean-field ansatz that allows for at most twosite magnetic unit cells; 47,50,52,54,58,59,61,64 very recently, this has been generalized to a Gutzwiller mean-field theory.…”
Section: Arxiv:10071949v2 [Cond-matsupr-con] 27 May 2011mentioning
confidence: 99%
“…At this electronic density, the Fermi surface is in agreement with experiments. Previously proposed three-orbital models [50,75] only contained the NN hybridization t 7 , but since NNN terms are included for the intra-orbital component, as well as for the hybridization between xz and yz, they should also be included in the hybridization with xy. It can be shown that these NNN terms with hopping t 8 turn out to be very important to provide the proper orbital character for the electron pockets when compared with LDA results.…”
Section: Real Spacementioning
confidence: 99%
“…A study based on the similar consideration for the interactions in the two-orbital model for pnictide superconductors with both electron and hole FS has been carried out from the strong coupling expansion 34 . We carry out the investigation using the FLEX approximation [35][36][37] , in which the Green's function and the spin/charge fluctuations are determined selfconsistently. Here, we consider the following spin fluctuationsχ s (q, iω n ) and charge fluctuationsχ c (q, iω n ):…”
Section: Model and Flex Methodsmentioning
confidence: 99%